Exploring the Role of Government Expenditure and Fintech in Environmental Quality: Evidence from Pakistan - Farooq, Fatima; Shah, Said Zamin; Nousheen, Asma; Faheem, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
The goal of achieving lower carbon emissions has recently become a hotly debated topic, and various studies have empirically assessed the repercussion of different economic variables on environment. This study examines the aftermath of GDP, government expenditure (GOE), FDI, and Fintech on CO2 in Pakistan from 1995 to 2023 by adopting the NARDL technique. The NARDL findings revealed that in positive shocks, GOE played a beneficial role in minimizing CO2 emissions, yet in negative shocks, GOE enhanced pollution levels in Pakistan. Moreover, FDI and GDP enhance environmental degradation, while Fintech mitigates CO2 emissions. These findings provide valuable insights for policy making. These findings also suggest that Pakistan should focus on reallocating government expenditures to green investments.